Elevated blood pressure and its relationship with bodyweight and anthropometric measurements among 8-11-year-old Indonesian school children - Nawanto Agung Prastowo; Ignatio Rika Haryono (SAGE Publishing, 2020)
Objective: Increased prevalence of elevated blood pressure in children and adolescents was associated with increased body weight and measures. Also, prevalence of elevated blood pressure varies between countries. This study is to investigate the prevalence of elevated blood pressure in Indonesian children and its relationship with bodyweight and anthropometric measures. Methods: This cross-sectional study involved 1010 elementary students aged 8-12 years (479 girls, 531 boys). The anthropometric measures and blood pressure were assessed. Elevated blood pressure (EBP) was determined if at the 90th percentile or above for gender, age, and height. Independent t-test, Chi-square, Pearson correlation, and multivariate logistic regression were applied. Significance was determined at p<0.05. Results: Overall prevalence of EBP was 28.8% (35.9% in girls, 22.4% in boys). BMI, waist circumference (WC), waist to height ratio (WHtR), and abdominal skinfold had significant correlation with EBP. Elevated BP was higher in overweight and obesity than in normoweight (60.5% vs 39.5%, p=0.00). In girls, the OR of EBP for overweight and obesity were 2.33 (95% CI 1.40 - 3.87, p=0.03) and 3.44 (95% CI 1.98 - 5.99, p=0.00)  whereas in boys were 4.26 (95% CI 2.20 - 8.28, p=0.00) and 8.82 (95% CI 5.10 - 15.38, p=0.00). Conclusions: Prevalence of EBP in Indonesian school children aged 8-11 years was higher and more prevalent in overweight/obesity and in girls. Anthropometric measures were correlated with EBP.